Multi-mode operation of a Liquid Air Energy Storage (LAES) plant providing energy arbitrage and reserve services – Analysis of optimal scheduling and sizing through MILP modelling with integrated thermodynamic performance - Vecchi, Andrea; Naughton, James; Li, Yongliang; Mancarella, Pierluigi; Sciacovelli, Adriano (Energy (Oxford), 2020)
Energy storage competitiveness is ubiquitously associated with both its technical and economic performance. This work investigates such complex techno-economic interplay in the case of Liquid Air Energy Storage (LAES), with the aim to address the following key aspects: (i) LAES optimal scheduling and how this is affected by LAES thermodynamic performance (ii) the effect of LAES sizing on its profitability and performance (iii) overall techno-economic assessment of LAES multi-mode operation when providing energy and reserve services. To address these aspects, a Mixed Integer Linear Programming-based optimisation tool has been developed to simulate LAES operation throughout a year while including detailed thermodynamic constraints, thus allowing an accurate performance estimation. The results demonstrate that considering LAES thermodynamic performance in the optimisation ensures a feasible dispatch profile thus avoiding loss of revenues, especially for the multi-mode cases. However, while operation with arbitrage and a portfolio of reserve services is financially promising, it also deteriorates LAES roundtrip efficiency; therefore, a techno-economic balance should be sought. In terms of design, the possibility of independently sizing LAES charge and discharge power is key for tailoring the plant to the specific operating mode. Furthermore, storage energy capacities greater than 2–3 h do not significantly increase LAES profitability under the market conditions considered. •LAES multi-mode operation for energy arbitrage and reserve services is assessed.•A novel MILP optimisation including LAES thermodynamic constraints is formulated.•Against traditional models we get 10% lower revenues, but feasible dispatch profile.•Multi-mode operation may allow payback time below 20 years.•LAES power sizing allows optimal design which depends on the operating strategy.